Quality of life and sexual dysfunction in cervical cancer survivors - Rai, Snigdha (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aim: To evaluate the quality of life and sexual dysfunction in cervical cancer survivors. Methods: This is a cross sectional study conducted in Bhaktapur Cancer Hospital from 14 th January to 13 th April 2021. Total 136 patients treated for cervical cancer without other coexisting cancers and psychological disorders were interviewed. Independent t test was used to compare means in two categories while ANOVA to compare mean in more than two categories like treatment. Result: Out of 136 cervical cancer survivors 80% were from hilly region, 75% were diagnosed in late stage of disease and average age was 50 years. Total mean FACT-Cx score was 61.1±14.8, with lowest score in physical wellbeing (8.4±5.5) and highest in social and family wellbeing (18.5±6.2); and 94.8% of the patients had sexual dysfunction. Conclusion: This study indicated that the quality of life and sexual function were very low among cervical cancer survivors. Need of counseling regarding the general health and sexual health among cervical cancer is observed.